LIMESTONE PURITY AS THE DECISIVE FACTOR FOR ITS CONSUMPTION IN THE FLUE GAS DESULPHURISATION PROCESS - Bricl, Martin (Journal of Energy Technology, 2023)
The wet flue gas cleaning process in thermal power plants uses limestone reagent, which is ground and mixed with process water, before coming in contact with flue gases, in order to form a homogeneous suspension, which then absorbs the gaseous acid components in the flue gas cleaning process in thermal power plants (mainly sulphur dioxide) from the flue gas stream. The purity of the limestone has a significant effect on its consumption, as cleaner limestone enables the absorption of a larger amount of acidic components from the flue gas stream, with lower total consumption of the reagent - i.e. limestone.